2021
DOI: 10.3390/designs5010007
|View full text |Cite
|
Sign up to set email alerts
|

Is Innovation Redesigning District Heating? A Systematic Literature Review

Abstract: The district heating (DH) industry has been characterized by continuous innovation for several decades, but there is limited knowledge on the characteristics of the sector’s innovation activities, arguably the most important information for understanding how the sector can continue to develop and further support the energy transition of society. We perform a systematic literature review (SLR) to identify the types of innovation, the levels of innovation and the relation between different innovations in the DH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In parallel, the DH companies must come closer to their customers and offer them new services (generating new revenues and reducing costs). The challenge of Capital Expenditures (CAPEX) is often neglected in the extremely infrastructure intensive DH industry [20] and by the academic community. Large production plants are expensive but will gradually be phased out when the 4GDH and 5GDH are phased in.…”
Section: District Heating Networkmentioning
confidence: 99%
“…In parallel, the DH companies must come closer to their customers and offer them new services (generating new revenues and reducing costs). The challenge of Capital Expenditures (CAPEX) is often neglected in the extremely infrastructure intensive DH industry [20] and by the academic community. Large production plants are expensive but will gradually be phased out when the 4GDH and 5GDH are phased in.…”
Section: District Heating Networkmentioning
confidence: 99%
“…By evaluating the transition in DHSs, it is shown that preliminary changes can mostly be characterized as incremental instead of disruptive. [28] DH is regarded as an economical, safe, and reliable technology for urban areas. However, as the complexity of the heating sector is high the transition to renewable sources is challenging, although a transition is supported by the public if the costs of a new supply are competitive compared to the costs of the current supply.…”
Section: Requirements For the Transition In Dhssmentioning
confidence: 99%
“…The change from fossil to non-combustion renewable heat sources is identified as a major topic for DH research [28]. Depending on the type of heat source, different constraints and requirements go along with the technologies.…”
Section: Technical Requirementsmentioning
confidence: 99%
See 2 more Smart Citations